Finite element analysis of composite slabs - Muhammad Aizat, Meor Hamzah (2019)
A finite element (FE) analysis of steel-concrete composite slab with profiled deck is presented in this paper. A FE software package, of ABAQUS, was used to develop the models. 3D FE models of consists of normal composite slabs and composite slabs strengthened with cold formed C-channels were developed. Besides the influence of C-channel, the influence of the composite slabs span also was investigated. The FE models considered materials and geometrical nonlinearities. Furthermore, appropriate contact interactions between components interfaces were assigned in the FE models of the composite slabs. The modelling techniques used to develop the proposed FE models of the composite slabs were verified based on disparate experimental test results. The disparate test results were obtained according to an experimental program on composite slabs under four-point bending test conducted by Marimuthu et al. (2007). Finite element analysis results demonstrated load-displacement curve of the composite slab. It is concluded that the composite slab showed significant improvement in strength by adding C-channel.